Perancangan dan Pengembangan Prototipe Pengelolaan E-Wallet Seluler Menggunakan Teknologi NFC - Lubis, Ika Rahmadani; Rahmah, Maulidya; Khair, Rizaldy (AI Society & STMIK Indonesia, 2024)
In the era of digitalization, the need for innovation in financial management has become increasingly urgent. With the emergence of E-wallets as a digital payment solution, the efficiency and security of transactions have become primary focuses. Therefore, this research plays a crucial role in presenting an innovative solution by designing and developing a mobile application prototype that integrates E-wallet management with Near Field Communication (NFC) technology. The urgency of this research is highlighted by the increasing use of E-wallets, which indicates that digital financial solutions are gaining wider acceptance in society. In this context, the integration of NFC becomes relevant as it offers higher security and enables more efficient transactions. This study aims to address the growing market demand for digital payment solutions that are fast, secure, and user-friendly. The objective is to design and develop a mobile application prototype that not only simplifies E-wallet management but also leverages the advantages of NFC technology. The goal is to provide users with a more convenient and secure transaction experience. Thus, this research is expected to increase the adoption of E-wallets among the general public. The result of this research is a mobile application prototype integrated with NFC technology for E-wallet management.